2006
DOI: 10.1029/2005gl024759
|View full text |Cite
|
Sign up to set email alerts
|

A cellular automaton for the factor of safety field in landslides modeling

Abstract: [1] Landslide inventories show that the statistical distribution of the area of recorded events is well described by a power law over a range of decades. To understand these distributions, we consider a cellular automaton model based on a dissipative dynamical variable associated to a time and position dependent factor of safety. The model is able to reproduce the complex structure of landslide distribution, as experimentally reported. In particular, we investigate the role of the rate of change of the system … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 27 publications
3
31
0
Order By: Relevance
“…2a, for a small value of ν, p(τ ) exhibits a linear regime in a log-log scale -that means a power-law regime in a linear scale -for recurrence time intervals that enlarge by increasing the threshold q. We note that in the limit of small values of ν, the model resembles the results of the OFC model (Olami et al, 1992), as extensively discussed in previous works (Piegari et al, 2006a(Piegari et al, , 2009a. Thus, in this regime p(τ ) is expected to be characterized by a power-law regime according to SOC-like models proposed for explaining recurrence time statistics of earthquakes and solar flares (Sanchez et al, 2002;Corral, 2004;Pacuzski et al, 2005).…”
Section: Analysis Of Varying Threshold Valuessupporting
confidence: 74%
See 2 more Smart Citations
“…2a, for a small value of ν, p(τ ) exhibits a linear regime in a log-log scale -that means a power-law regime in a linear scale -for recurrence time intervals that enlarge by increasing the threshold q. We note that in the limit of small values of ν, the model resembles the results of the OFC model (Olami et al, 1992), as extensively discussed in previous works (Piegari et al, 2006a(Piegari et al, , 2009a. Thus, in this regime p(τ ) is expected to be characterized by a power-law regime according to SOC-like models proposed for explaining recurrence time statistics of earthquakes and solar flares (Sanchez et al, 2002;Corral, 2004;Pacuzski et al, 2005).…”
Section: Analysis Of Varying Threshold Valuessupporting
confidence: 74%
“…In other words, we take into account non-conservative (dissipative) cases where the quantity C = nn f nn , which fixes the degree of conservation of the system, is less than 1, contrary to other approaches (Hergarten and Neugebauer, 2000;Hergarten, 2003). The role of the model parameter C has been investigated in previous works, where we found that the shape of the frequencysize probability distribution of landslide events is strongly affected by the values of C (Piegari et al, 2006a), while it is not significantly affected by the values of the coefficients f nn in the range of values that supply power-law distributions (Piegari et al, 2006b). In particular, only if C < 1 do our synthetic frequency-size distributions reproduce those from catalogues (Piegari et al, 2009a), pointing out the relevance of dissipative phenomena to landslide triggering.…”
Section: The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Lübeck (1997) conducted large-scale simulations of a similar Zhang sandpile and obtained exponents slightly higher than 1.2, which can go even higher for large driving rates ν. In a similar model that incorporated non-conservation, Piegari et al (2006) obtained power-law exponents that approach 1.6 in the conservative limit for the same order or magnitude of ν that we used. The higher exponents and the effect of the driving rates are also verified by an equivalent conservative model and actual sand avalanche experiments by Juanico et al (2008), and in other asynchronous updating models (Paguirigan et al, 2015).…”
Section: Model Specificationsmentioning
confidence: 99%
“…The sandpile model, introduced as a representative system for illustrating self-organized criticality (SOC; Bak et al, 1987), has opened up new avenues for the use of discrete cellular automata (CA) models in capturing the salient features of many systems in nature (Olami et al, 1992;Drossel and Schwabl, 1992;Malamud and Turcotte, 2000;Piegari et al, 2006;Juanico et al, 2008). Seismicity, which is rife with power-law statistical distributions (Saichev and Sornette, 2006), is an interesting test case for such approaches.…”
Section: Introductionmentioning
confidence: 99%